Magnetic Flux and Helicity of Magnetic Clouds - Démoulin, Pascal (2016)
Magnetic clouds (MCs) are formed by flux ropes (FRs) launched from the Sun as part of coronal mass ejections (CMEs). They carry away a large amount of magnetic flux and helicity. The main aim of this study is to quantify these amounts from in situ measurements of MCs at 1 AU. The fit of these data by a local FR model provides the axial magnetic field strength, the radius, the magnetic flux, and the helicity per unit length along the FR axis. We show that these quantities are statistically independent of the position along the FR axis. We then derive the generic shape and length of the FR axis from two sets of MCs. These results improve the estimation of magnetic helicity. Next, we evaluate the total magnetic flux and helicity that cross the sphere of radius of 1 AU, centred at the Sun, per year and during a solar cycle. We also include in the study two sets of small FRs that do not have all the typical characteristics of MCs. While small FRs are at least ten times more numerous than MCs, the magnetic flux and helicity are dominated by the contribution from the larger MCs. In one year they carry away the magnetic flux of about 25 large active regions and the magnetic helicity of 200 of them. MCs carry away an amount of unsigned magnetic helicity similar to the amount estimated for the solar dynamo and that measured in emerging active regions.